2019
DOI: 10.1016/j.jbusres.2018.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' ethical perceptions of social media analytics practices: Risks, benefits and potential outcomes

Abstract: The increased leveraging of social media by organizations to derive business value has created concerns about the practice of social media analytics (SMA). While SMA may be beneficial for organizations and consumers alike, there is concern that it is not practiced with ethical care. In this study, we identify and model outcomes of ethical perceptions of SMA practices and organizational trustworthiness with data collected from 316 social media users. We also examine the roles of perceived risk and benefits in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 75 publications
2
10
0
1
Order By: Relevance
“…The current study revealed that perceived risk significantly mediates the relationship between perceived ethicality of social media analytics and marketing discomfort and consumer self-disclosure. These outcomes are consistent with previous studies (Michaelidou & Micevski, 2019). Michaelidou & Micevski (2019) penned down that unfavorable social media analytics practices lead to an increase in the perceived risk of the consumer and eventually impact the consumer willingness to disclose about themselves.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The current study revealed that perceived risk significantly mediates the relationship between perceived ethicality of social media analytics and marketing discomfort and consumer self-disclosure. These outcomes are consistent with previous studies (Michaelidou & Micevski, 2019). Michaelidou & Micevski (2019) penned down that unfavorable social media analytics practices lead to an increase in the perceived risk of the consumer and eventually impact the consumer willingness to disclose about themselves.…”
Section: Discussionsupporting
confidence: 92%
“…These outcomes are consistent with previous studies (Michaelidou & Micevski, 2019). Michaelidou & Micevski (2019) penned down that unfavorable social media analytics practices lead to an increase in the perceived risk of the consumer and eventually impact the consumer willingness to disclose about themselves. Similarly, (Jacobson et al, 2020) highlighted that consumers usually evaluate the risk and benefits of sharing information on social media.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Past research has shown the importance of social media analytics to understand the perception and to identify the events/factors influencing a brand or product performance (Park et al, 2016;Kaplan and Haenlein, 2010). However, most research are focused toward the customer's perception toward the brand or product (Michaelidou and Micevski, 2019;Rose et al, 2019). Very few studies on social media analytics are focused toward the startup ecosystem.…”
Section: Literature Reviewmentioning
confidence: 99%